Prognostic Significance of Systemic Inflammatory Response in Cases of Temporal Bone Squamous Cell Carcinoma. (4th February 2021) - Komune, Noritaka; Sato, Kuniaki; Hongo, Takahiro; Miyazaki, Masaru; Masuda, Shogo; Koike, Kensuke; Uchi, Ryutaro; Tsuchihashi, Nana Akagi; Noda, Teppei; Kogo, Ryunosuke; Wakasaki, Takahiro; Yasumatsu, Ryuji; et al.
Abstract : Objective/Hypothesis: Squamous cell carcinoma (SCC) of the temporal bone is an extremely rare condition. This rarity has led to a delay in the establishment of a standard treatment protocol and adequate staging system. Identification of prognostic markers of this disease from a variety of fields is desirable in the establishment of treatment guidelines for temporal bone SCC. The aim of this study is to assess the prognostic role of inflammation‐based prognostic scores in cases of temporal bone SCC. Study Design: Case reries with chart review. Methods: A total of 71 cases of primary malignancy eligible for curative treatment at a single tertiary medical institute were retrospectively analyzed. Univariate and multivariate regression analyzes were used to investigate the association between the inflammation‐based scores and 5‐year overall survival. Results: Univariate Cox regression analyzes showed that a high neutrophil‐to‐lymphocyte ratio, high platelet‐to‐lymphocyte ratio, low lymphocyte‐to‐monocyte ratio, a Glasgow prognostic score of 2, and the systemic inflammation score of 2 were significantly associated with a poor prognosis, as well as a classification of T4 stage, presence of cervical lymph node metastasis, high white blood cell counts, and high C‐reactive protein levels. The multivariate analysis showed that a clinical stage of T4 and a systemic inflammation score of 2 were independent prognostic markers. Conclusions: Inflammation‐based prognostic markers are associated with the survival of patients with temporal bone SCC, as well as other head and neck SCCs. Level of Evidence: 4 Laryngoscope, 131:1782–1789, 2021